A comparison of risk factors and prognosis between intra and extracranial acute atherosclerotic stroke in the Turkish population: a prospective study. (2nd October 2016) - Keheya, Sezgin; Tekatas, Aslan; Aynacı, Özer; Utku, Ufuk; Solmaz, Volkan
Abstract : Background: The aim of this study was to compare the differences in risk factors and prognosis between acute stroke caused by definitive intracranial atherosclerosis (ICAS) or extracranial atherosclerosis (ECAS) in the Turkısh population. Methods : This study was prospectively designed in a single centre and conducted with patients who were hospitalised due to acute ischaemic stroke. Inclusion criteria were the diagnosis of atherosclerotic ischaemic stroke, defined as more than 50% stenosis or occlusion in the arterial structure supplying the ischaemic area, having excluded other possible causes. Results : Information on 58 ICAS and 57 ECAS stroke patients was collected in a 13-month period. The ECAS patients had male gender predominance ( p  = 0.003). Ageing, stroke history and hyperlipidaemia were related with stroke severity in ECAS, and gender was associated with severity in ICAS. Hypertension and being female were related with poor prognosis in ICAS ( p  = 0.081 vs. 0.087). Congestive heart failure ( p  = 0.002) was associated with poor prognosis and alcohol with a favourable outcome ( p  = 0.087) in ECAS. Stroke severity was related with poor prognosis in both groups ( p  < 0.001). Conclusions : The prevalence of risk factors differs between ICAS and ECAS, and their influence differs for stroke severity and prognosis.